ChemInform Abstract: Catalytic Asymmetric [3 + 2]‐Cycloaddition for Stereodivergent Synthesis of Chiral Indolyl‐Pyrrolidines. Issue 24 (27th May 2016) - Arai, Takayoshi; Tokumitsu, Chihiro; Miyazaki, Tomoya; Kuwano, Satoru; Awata, Atsuko
Abstract: The asymmetric [3 + 2]‐cycloaddition of indolyl nitroalkene to iminoesters in the presence of nickel acetate and IAP ligand gives rise to pyrrolidines (III), whilst the copper‐catalyzed reaction in the presence of PBD ligand leads to endo‐products (VI).